THE INFLUENCE OF PRODUCT BRAND, QUALITY, AND PACKAGING ON CUSTOMER RESPONSE AND THE IMPLICATIONS ON THE LOYALTY OF MINIMARKETMINIMARKET MUSLIM CONSUMERS: SYSTEMATIC REVIEWS - SILVIA EKASARI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2022)
This economic business study aimed to identify brands' influence, product quality, and packaging on customer responses and implications for Muslim consumer loyalty in Minimarket. For this reason, we first collect data related to the above issues from various online data sources such as data sources based on Google Scholar publications, Google Docs, and other sources of academic literature. After that, we continue with the analysis to get answers to the problems of this study. Data analysis started from a preliminary reading of the literature and connected with questions. Then analysis and in-depth interpretation are continued to get answers as the findings of this study. We selected secondary data according to the systematic review design model. Then we continue writing a report in a qualitative descriptive form with the principles of validity and reliability. Considering existing data, we report a very close influence between brand, quality, and product packaging on the response of Muslim customers, which lately has become a shopping trend among Muslim consumers.